Carbon dots for ultrastable solid‐state batteries. Issue 2 (7th March 2022) - Xu, Laiqiang; Tu, Hanyu; Zhu, Fangjun; Xiang, Yinger; Luo, Zheng; Fang, Susu; Deng, Wentao; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Among the solid electrolytes for solid‐state Li batteries, polymer electrolytes are actively explored on the basis of the good interfacial contact and easy making, while it is still constrained by slow ionic transport and low lithium ion transference number. Herein, functional carbon dots‐based Li + conductor (CD‐Li) is designed to improve the dynamics and selectivity of Li + transport in polyethylene oxide (PEO) electrolyte. High ionic conductivity (1.0 × 10 −4  S/cm, 25 °C) and Li + transference number (0.60) were successfully achieved within the CD‐Li‐based PEO composite electrolyte, which could be attributed to the enhanced chain movement and the limited motion of anion. Moreover, the characteristics of big volume of individual anions of CD‐Li can provide more free Li + . As well, benefiting from the existence of F atom in the CD‐Li, in‐situ constructed LiF‐containing interfacial layer is in favor of maintaining the interface stability and facilitating the rapid transmission of Li ions. The composite electrolyte with CD‐Li can address the ionic conductivity issues accompanied with strengthening the interfacial stability. The distinctive composite electrolyte realizes the stable cycle performance for Li/LiFePO4 and Li/LiNi0.5 Co0.2 Mn0.3 O2 batteries. The exploration of multifunctional carbon dot fillers provides new ideas for the efficient development of composite electrolytes. Abstract : A novel carbon dots‐based Li + conductor is synthesized to construct PEO composite electrolytes with highly selective fast Li ion transport. The characteristics of big volume of individual anions of CD‐Li enable the composite electrolyte with high Li + transport number. Moreover, the in‐situ formed LiF‐engineered interfacial layer is maintaining the interfacial stability.